Trade Diversion and Production Sharing - Sven W. Arndt (Claremont McKenna College, Department of Economics, 2004)
This paper examines the repercussions of cross-border production sharing for the welfare effects of preferential trade liberalization. In a general-equilibrium context, a free trade agreement (FTA), which incorporates production sharing, raises the likelihood of welfare improvement. Thus, two members of a free trade area, who each have comparative disadvantage in the production of a final product relative to a nonmember, may nevertheless enjoy net trade creation if they jointly possess comparative advantage in key components of that product. At a minimum, cross-border production sharing reduces the trade-diverting elements of an FTA. It follows, that rules of origin, viewed as constraints on cross-border fragmentation, augment the negative, tradediverting elements of free trade areas.
Keywords: F15; F13; F11; 330; Trade Diversion; Free Trade Areas; Fragmentation; Production Networks; Aussenhandelspräferenz; Freihandelszone; Aussenhandelseffekt; Internationale Arbeitsteilung